Dental caries and mean values of DMFT among children with cerebral palsy: a systematic review and meta-analysis - Melkamu Aderajew Zemene; Anteneh Mengist Dessie; Denekew Tenaw Anley; Mengesha Assefa Ahunie; Natnael Atnafu Gebeyehu; Getachew Asmare Adella; Gizachew Ambaw Kassie; Misganaw Asmamaw Mengstie; Mohammed Abdu Seid; Endeshaw Chekol Abebe; Molalegn Mesele Gesese; Natnael Amare Tesfa; et al. (BMC, 2024)
Abstract Introduction One of the most prevalent causes of physical disability in children is cerebral palsy (CP), which is a series of complicated neurological disorders. Children with cerebral palsy suffer from multiple problems and potential disabilities, including dental caries. Hence, this study aimed to determine the pooled prevalence of dental caries and mean DMFT (Decayed, Missed, and Filled Permanent Teeth) among children with cerebral palsy in Africa and Asia. Methods A comprehensive search of the literature was made to locate relevant studies in PubMed/Medline, HINARI, Web of Science, Science Direct, the Cochrane Library, the Worldwide Science Database, and Google Scholar. The data were extracted in Microsoft Excel and transferred to Stata version 17 software for further analysis. A random-effect model was employed to estimate the pooled prevalence of dental caries and the pooled mean value of DMFT among children with cerebral palsy in Africa and Asia. Heterogeneity between studies was checked using the Cochrane Q test and I2 test statistics. Sub-group analysis by continent was done, and sensitivity analysis was checked. A small study effect was checked using Egger's statistical test at the 5% level of significance. Results In this study, 25 original studies conducted in 17 countries in Africa and Asia that fulfilled the eligibility criteria were included in the review. The overall pooled prevalence of dental caries in Africa and Asia among children with cerebral palsy was 55.6% (95% CI: 42.4, 68.8). The pooled prevalence of dental caries among children with cerebral palsy in Africa was 42.43% (95% CI: 30.39, 54.58), and it was slightly higher in Asia with 64% (95% CI: 48.32, 79.72). In the random effect model analysis, the pooled mean DMFT of dental caries in children with cerebral palsy was 2.25 (95% CI: 1.86, 2.64). The pooled mean DMFT in Africa was 1.47 (95% CI: 0.86, 2.09), and in Asia it was 3.01 (95% CI: 2.43, 3.60). Conclusion In this study, we found that children with cerebral palsy experienced an alarming rate of dental caries. In these settings, dental caries affected roughly more than half of the children with cerebral palsy. Hence, oral health promotion initiatives should target children with CP, and this group of children must receive early preventive dental care.